Analisis Faktor-Faktor Yang Mempengaruhi Minat Beli Sepeda Listrik Terhadap Masyarakat Kraksaan - Hamzah, Moh; Junaidi, Ahmad; Fattah, Abdul; Bayu, Septian; Rizal, Moh; Ubaidillah, Ubaidillah (New Economy, 2025)
Technological developments are increasingly sophisticated. Likewise, sophistication is developing in vehicle parts. What were originally fuel-powered vehicles have now been modernized with electric vehicles that only rely on electricity as a charger. Therefore, researchers aim to find out the factors that influence the interest in buying electric bicycles among the people of Paiton. This research uses quantitative methods. The population in this research is the Paiton community who own electric bicycles. In this research, the sampling method used is the simple random sampling method. The simple random sampling method (Simple Random Sampling) is a sampling technique that is completely based on providing equal opportunities to the entire population (Bambang Sugeng, 2022). This research uses the Lemeshow formula, because the sample population is unknown. This research used a sample of 96 respondents. In accordance with calculations using the Lemeshow formula. The data analysis technique used is multiple linear regression analysis with the help of SPSS software. The research results show that taste, price and income do not influence people's interest in buying electric bicycles.